THE INFLUENCE OF DIGITAL LEADERSHIP, NEW ORGANIZATIONAL CULTURE AND TEAMWORK ON JOB SATISFACTION OF OFFICE EMPLOYEES SOCIAL SERVICES DEPARTMENT OF SERDANG BEDAGAI REGENCY - Yana Puspita Ningrum; Suhaila Husna Samosir; Julianto Hutasuhut; Mhd. Dhani Habra (PT. Radja Intercontinental Publishing, 2026)
This study aims to determine and analyze the influence of Digital Leadership, New Organizational Culture and Teamwork on Job Satisfaction of Employees at the Social Service Office of Serdang Bedagai Regency. This study uses a quantitative approach. The population in this study were all employees of the Social Service Office of Serdang Bedagai Regency, totaling 38 respondents. The sampling technique used was saturated sampling, so that all members of the population were used as research samples. Data collection techniques were carried out by observation, as well as questionnaires with a Likert Scale data measurement scale. Data analysis techniques used validity, reliability and classical assumption tests. The data analysis method used multiple linear regression with the help of the SPSS version 25 program. The results of this study indicate that Digital Leadership has a positive and significant effect on Employee Job Satisfaction with a t-value of 3.470 and a significant value of 0.001 <0.05. New Organizational Culture has a positive and significant effect on Employee Job Satisfaction with a t-value of 3.308 and a significant value of 0.002 <0.05. Teamwork has a positive and significant effect on Employee Job Satisfaction with a t-value of 3.412 and a significant value of 0.002 < 0.05. Simultaneously, Digital Leadership, New Organizational Culture and Teamwork have a positive and significant effect on Employee Job Satisfaction at the Social Service Office of Serdang Bedagai Regency .